PENGAKUAN, PENGUKURAN, DAN PENGUNGKAPAN INTELLECTUAL CAPITAL TERHADAP PENILAIAN KINERJA PERUSAHAAN - HALIM ADI GUNAWAN (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Human resources is one of the assets to run the company's operations. various expenditures for human resource development was essential to improve performance. For that, all costs to improve the capabilities of intellectual capital and deserve to be recognized and capitalization. But that deserve to be explored further is how the recognition, measurement and disclosure of intellectual capital that can be identified how big is able to contribute to the company’s financial statements. Recognition of intellectual capital worth it considering the company also issued a number of costs to improve the capabilities possessed intellectual capital. While for intellectual capital measurement can be done with various methods but among these methods, then the method return-on-assets (ROA) can provide more comprehensive information. ROA is calculated excess return of tangible assets owned by the company and take it as intangible assets to count as intellectual capital. Recognition, measurement, and disclosure of intellectual capital has an influence on the company's performance appraisal can provide information about the feedback (contribution) of the intellectual capital to the achievement of company performance. Through the recognition, measurement, and disclosure of intellectual capital is an assessment of the performance can be explained by informative and detailed.